Fertilización del hibrido de maíz (Zea mays) INIAP H-553 con fuentes nitrogenada en el cantón Ventanas - Arechua Gonzalez, Aracely Azucena (2012)
The corn (Zea mays), native from America, one represents from the most valuable contributions to the world alimentary security. Together with the rice and the wheat they are considered as three o'clock gramineous more cultivated in the world. The fertilization is one of the decisive factors to achieve high yields and among the macro elements, the nitrogen is one of the obstacles in the floors of the Ecuadorian coast, due to its drop he/she witnesses and readiness, reason for which is necessary to apply an appropriate supply of this element. The present investigation work has more than enough Fertilization of the Hybrid one of corn (Zea mays) INIAP H-553 with sources nitrogenadas in the canton Ventanas, was carried out in Mrs. Margarita property González Jara, located in the Enclosure Big Cachely of the Canton Ventanas, with the following objectives: It evaluated the sources nitrogenadas in the agronomic behavior of the hybrid one of corn INIAP H-553. It established the effect of the best nitrogen source applied in the hybrid one It evaluated the sources nitrogenadas in the production of the hybrid one of corn INIAP H-553 It determined the effect of the sources nitrogenadas in the encame of the hybrid one of corn INIAP H-553 He/she carried out an analysis of the costo/beneficio of the treatments proposed in the study. It was used as treatments in studies 5 nitrogen sources in the Hybrid of corn INIAP H-553. Urea Ammonium nitrate Ammonium sulfate Nitrate of calcium Nitrate of magnesium Design of blocks was used totally at random with 5 more treatments a comparison witness and 4 repetitions. According to the results we could say that the use of nitrate of calcium is a good alternative in the cultivation of corn, since the alone use of urea like he/she makes it the farmer it can take to acidify the floors.